Site and size of lesion predict post-stroke spasticity: A retrospective magnetic resonance imaging study - Songjin Ri; Anatol Kivi; Peter P. Urban; Thomas Wolf; Jörg Wissel (Medical Journals Sweden, 2020)
Objective: Clinical parameters for prediction of post-stroke spasticity are well established. This report introduces 2 brain magnetic resonance imaging (MRI) parameters (infarct volume and topographic distribution) as post-stroke spasticity predictors. Methods: Topographic and volumetric data from brain MRI for 98 patients with ischaemic stroke with spasticity, prevalent within the first 5 days after stroke and 6 months after stroke, were retrospectively correlated using Chris Rorden's MRIcron software. Results: Lesions within the supply territory of the middle cerebral artery involving the pyramidal tract were more frequently associated with spasticity than without spasticity (30.8% vs 5.1%). Middle cerebral artery lesions not affecting the pyramidal tract were found more often in patients without spasticity (49.2% vs 10.3%). Spasticity showed a significantly higher association with middle cerebral artery+pyramidal tract/internal capsule lesions than did "no spasticity" (97.5% vs 18.7%, p < 0.01), and lesion volumes were significantly larger in patients with spasticity than in those without spasticity (p < 0.01). Conclusion: Large stroke volumes might predict post-stroke spasticity if the lesion is > 3 cm3 in size and if the lesion is located within the middle cerebral artery territory with involvement of the pyramidal tract and/or internal capsule. Lesion size ≤ 2 cm3 outside the middle cerebral artery territory is associated with lower risk of post-stroke spasticity.